Students Concepts Understanding Through Inquiry Learning Model Based on Local Wisdom in the Theme of "Heat and Its Transfer" - Nadhifatul Ayun, Silva; Alimah, Siti; Dharma Putra, Ngurah Made (Journal of Primary Education, 2020)
This study aims to analyze the improvement and profile of students' conceptual understanding through a local wisdom-based inquiry model. This research used mixed method with a sequential explanatory design. The population in this study were all class 5 students from six elementary schools in Mayong Jepara. The selection of sample of this study used simple random sampling technique. The study has two sample of class 5 of SD Negeri 2 and SD Negeri 3 Mayong Lor with 27 student and 30 student as the sample, respectively. The first stage is a quantitative method in the form of a true-experimental design with a pre-test and post-test control group design type. Data collection was used test, to know the understanding of the student on heat transfer concept. Then completed using documentation and interview for qualitative stage. Then for data analysis was used n-gain test and description according to Miles and Hubermans models. Based on the conceptual understanding score shows the average score obtained by the experimental class student was increased from 51.48 to 77.41 and the control class obtained an average increase from 52.33 to 66.00. The results of the average difference test of students’ conceptual understanding show that the sig. (2-tailed) value generated is 0.001 < 0.05, it indicates H0 is rejected, which means that there is a difference in conceptual understanding between the inquiry class and the local wisdom-based inquiry class. The profile of concept understanding on each indicator of class 5 students on the theme of heat and its transfer through the inquiry model as a whole is included in the good category with a percentage of 79.32 and the results of the interviews showed that students are easier to understand the material conveyed through direct observation to the roof tile manufacturing company.